2007
DOI: 10.1016/j.vaccine.2007.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Detection of vaccinia virus DNA, but not infectious virus, in the blood of smallpox vaccine recipients

Abstract: The authors of a recent study suggested that the duration of deferral for blood donations by smallpox vaccinees should be extended, based on detection of vaccinia virus DNA in 5 blood samples by PCR and the potential for viremia. We found that 4 of 202 blood specimens (from 3 of 27 smallpox vaccinees) were positive for vaccinia virus DNA by PCR; none were positive for virus by culture. Throat swabs were negative by PCR and culture. Thus, while some blood specimens contained vaccinia virus DNA, infectious virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…To date, other studies have described the detection of OPV or PPV-DNA in the blood related with the acute-phase of the diseases. [15][16][17] Although other reports have described the circulation of PPV in Brazil, 8,10 our study is the first to specifically describe the detection of a PCPV in Brazil. The PPV phylogenetic-tree (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…To date, other studies have described the detection of OPV or PPV-DNA in the blood related with the acute-phase of the diseases. [15][16][17] Although other reports have described the circulation of PPV in Brazil, 8,10 our study is the first to specifically describe the detection of a PCPV in Brazil. The PPV phylogenetic-tree (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Nitsche et al 28 showed the longlasting DNAemia of the Cowpox virus in humans, and the presence of IgG and IgM were not sufficient to resolve infection. Other works involving VACV-vaccinated patients demonstrated viral DNA in blood until 20 days post-vaccination, 29,30 as well as in accidental post-vaccination VACV infections (eczema vaccinatum). 31 Interestingly, our results indicate that natural VACV infection follows an analogous model once viral DNA is detected until 1 month postinitial clinical symptoms in serum ( Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…In some studies, viraemia was detected by PCR up to 21 days following an immunisation [3]. Other authors did not succeed in detecting VACV DNA in the blood, or did so only in isolated cases, and even then, only in a short time interval after the vaccination [36,122,123]. Infectious virus could not be detected in these investigations.…”
Section: Assessmentmentioning
confidence: 94%